Colour Terms in Advertisements - Harutyunyan, Kristine (Armenian Folia Anglistika, 2015)
The present article focuses on the peculiarities of the usage of colour terminology in advertisements. We live in a colourful world and there are great many colour words to describe it. We also live in a world where advertisement has become an accompanying phenomenon of our everyday life. It is obvious that the language of advertising has its specific features and it seems worth trying to reveal the role and the meaning of the colours used in advertisements. Colour terms are known to be linguistic universals which have certain associations attached to each of them. We may suppose that the colours that are mostly used in the advertisements are the basic colour terms. The spheres where we expect to find wider usage of colour terms should be the ones connected with fashion industry.
Keywords: colour terms; advertisements; hue; lightness; saturation; symbolism